Jets and jet substructure at future colliders - Bonilla, Johan; Chachamis, Grigorios; Dillon, Barry M.; Chekanov, Sergei V.; Erbacher, Robin; Gouskos, Loukas; Hinzmann, Andreas; Höche, Stefan; Huffman, B. Todd; Kotwal, Ashutosh. V.; Kar, Deepak; Kogler, Roman; et al. (Frontiers in physics, 2022)
Even though jet substructure was not an original design consideration for the Large Hadron Collider (LHC) experiments, it has emerged as an essential tool for the current physics program. We examine the role of jet substructure on the motivation for and design of future energy Frontier colliders. In particular, we discuss the need for a vibrant theory and experimental research and development program to extend jet substructure physics into the new regimes probed by future colliders. Jet substructure has organically evolved with a close connection between theorists and experimentalists and has catalyzed exciting innovations in both communities. We expect such developments will play an important role in the future energy Frontier physics program.
Gesehen am 24.08.2022